Efficacy and safety of brolucizumab versus aflibercept in eyes with polypoidal choroidal vasculopathy in Japanese participants of HAWK - Ogura, Yuichiro; Jaffe, Glenn J; Cheung, Chui Ming Gemmy; Kokame, Gregg T; Iida, Tomohiro; Takahashi, Kanji; Lee, Won Ki; Chang, Andrew A; Monés, Jordi; D’Souza, Divya; Weissgerber, Georges; Gedif, Kinfemichael; et al. (British journal of ophthalmology, 2022)
PurposeTo compare the efficacy and safety of brolucizumab versus aflibercept in eyes with polypoidal choroidal vasculopathy (PCV) over 96 weeks in the HAWK study.DesignHAWK was a global, 2-year, randomised, double-masked, multicentre phase III trial in participants with neovascular age-related macular degeneration.MethodsOf the Japanese participants with PCV, 39 received brolucizumab 6 mg and 30 received aflibercept 2 mg. After 3 monthly loading doses, brolucizumab-treated eyes received an injection every 12 weeks (q12w) but were adjusted to q8w if disease activity was detected. Aflibercept-treated eyes received fixed q8w dosing. Mean change in best-corrected visual acuity (BCVA), the proportion of participants on q12w, retinal thickness, retinal fluid changes and safety were assessed to Week 96.ResultsMean change in BCVA (early treatment diabetic retinopathy study (ETDRS) letters) from baseline to week 48/week 96 was+10.4/+11.4 for brolucizumab and +11.6/+11.1 for aflibercept. For brolucizumab-treated eyes, the probability of only q12w dosing after loading through week 48 was 76%, and 68% through week 96. Fluid resolution was greater with brolucizumab than aflibercept: respective proportions of eyes with intraretinal fluid and/or subretinal fluid were 7.7% and 30% at week 48% and 12.8% and 16.7% at week 96. Brolucizumab exhibited an overall well-tolerated safety profile despite a higher rate of intraocular inflammation compared with aflibercept.ConclusionIn Japanese eyes with PCV, brolucizumab q12w/q8w monotherapy resulted in robust and consistent BCVA gains that were comparable to q8w aflibercept dosing. Anatomical outcomes favoured brolucizumab over aflibercept, with 76% of brolucizumab participants maintained on q12w dosing after loading to week 48.